Analyzing YG Entertainment's Financial Impact: Addressing Brand Image Decline and Solutions - Sarjono, Haryadi; Zetta, Azlia; Sitorus, Grace Cynthia Magdalena; Soeratin, Boyke Setiawan (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
This research explores the impact of YG Entertainment's strategy in 2019 on the company's financial condition and image after a series of problems involving its artists in 2019. YG Entertainment, a prestigious South Korean entertainment company, faced major challenges, including prostitution-related controversies, drug scandals, and tax problems. These problems caused a decline in the value of the company's shares and raised concerns among investors and fans. This research aims to investigate the strategies implemented by YG Entertainment to recover from financial losses and assess the effect of these solutions on the company's financial condition. In addition, this research aims to measure the magnitude of losses experienced by YG Entertainment and the extent of financial recovery after implementing the strategy. Next, this research explores the importance of brand image in influencing the financial condition of entertainment companies. The research findings serve as a source of knowledge for readers who want to understand real cases of how companies overcome crises and their sequential impacts. For the author, this research contributes to knowledge and learning in exploring the dynamics of the entertainment industry which is full of challenges. Further research explored the problems faced by YG Entertainment in 2019, with scandals involving prominent artists. The impact of this problems on the company's share value and market capitalization is discussed, showing the seriousness of the challenges faced by the entertainment giant. YG Entertainment's solution involves the debut of a new boy band, re-planning the presence of artists who have been absent for a long time, and renewing contracts. Research shows that this strategy produces a positive response.Overall, this research provides valuable insight into the dynamic relationship between brand image, financial condition, and crisis management in the entertainment industry, using YG Entertainment as a case study.